PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MELALUI IMPLEMENTASI MODEL PEMBELAJARAN MURDER PADA SISWA KELAS IX SMP N 7 MATARAM, NUSA TENGGARA BARAT - Suherni Suherni (STKIP PGRI SITUBONDO, 2021)
This study aims to determine the improvement of English learning outcomes through the implementation of the MURDER learning model for Class IX students of SMP N 7 Mataram, West Nusa Tenggara. The research was conducted in October 2020 in Class IX SMP N 7 Mataram with two cycles of Classroom Action Research (CAR). Based on the research, it can be seen that the application of the MURDER learning model can improve the English learning outcomes of Class IX students at SMP N 7 Mataram. During the first cycle of CAR, 80.95% of students had completed and 19.05% of students had not completed it. There was an increase of 47.62% of students completing the first cycle (from 33.33% of students completing before the CAR to 80.95% of students completing the first cycle of CAR). During the second cycle of CAR, there were 90.48% of students who had completed it and 9.52% of the students had not completed it. There was an increase of 9.53% of students completing the second cycle (from 80.95% of students completing the first CAR to 90.48% of students completing the second cycle of CAR).